FAM83H and Autosomal Dominant Hypocalcified Amelogenesis Imperfecta. (March 2021) - Wang, S.K.; Zhang, H.; Hu, C.Y.; Liu, J.F.; Chadha, S.; Kim, J.W.; Simmer, J.P.; Hu, J.C.C.
Autosomal dominant hypocalcified amelogenesis imperfecta (ADHCAI; OMIM #130900) is a genetic disorder exhibiting severe hardness defects and reduced fracture toughness of dental enamel. While the condition is nonsyndromic, it can be associated with other craniofacial anomalies, such as malocclusions and delayed or failed tooth eruption. Truncation mutations in FAM83H (OMIM *611927) are hitherto the sole cause of ADHCAI. With human genetic studies, Fam83h knockout and mutation–knock-in mouse models indicated that FAM83H does not serve a critical physiologic function during enamel formation and suggested a neomorphic mutation mechanism causing ADHCAI. The function of FAM83H remains obscure. FAM83H has been shown to interact with various isoforms of casein kinase 1 (CK1) and keratins and to mediate organization of keratin cytoskeletons and desmosomes. By considering FAM83H a scaffold protein to anchor CK1s, further molecular characterization of the protein could gain insight into its functions. In this study, we characterized 9 kindreds with ADHCAI and identified 3 novel FAM83H truncation mutations: p.His437*, p.Gln459*, and p.Glu610*. Some affected individuals exhibited hypoplastic phenotypes, in addition to the characteristic hypocalcification enamel defects, which have never been well documented. Failed eruption of canines or second molars in affected persons was observed in 4 of the families. The p.Glu610* mutation was located in a gap area (amino acids 470 to 625) within the zone of previously reported pathogenic variants (amino acids 287 to 694). In vitro pull-down studies with overexpressed FAM83H proteins in HEK293 cells demonstrated an interaction between FAM83H and SEC16A, a protein component of the COP II complex at endoplasmic reticulum exit sites. The interaction was mediated by the middle part (amino acids 287 to 657) of mouse FAM83H protein. Results of this study significantly extended the phenotypic and genotypic spectrums of FAM83H -associated ADHCAI and suggested a role for FAM83H in endoplasmic reticulum–to–Golgi vesicle trafficking and protein secretion (dbGaP phs001491.v1.p1).